Sengmaek-san-mediated Enhancement of Axonal Regeneration after Sciatic Nerve Injury in the Rat - Kyungmin Baek; Yoon Sik Kim; Ho Ryong Ryu; Hyun Kyung Jo; Jung Jo An; Uk Namgung; In Chan Seol (동의생리병리학회지, 2008)
Sengmaek-san(Shengmai-san; SMS) is used in oriental medicine as one of the key herbal medicine for treating diverse symptoms including cardiovascular and neurological disorders. In the present study, the effects of SMS on axonal regeneration were investigated in the rat model given sciatic nerve injury. SMS treatment enhanced axonal regrowth into and the number of non-neuronal cells in the distal area after crush injury. GAP-43 protein levels were increased in the injured sciatic nerve compared to intact nerve and further upreguated by SMS treatment. GAP-43 protein was increased similarly in the dorsal root ganglion (DRG) at lumbar 4 - 6 by nerve injury and SMS treatment, suggesting GAP-43 induction at gene expression level. SMS-mediated increase in phospho-Erk1/2 protein was observed in the DRG as well as in the injured nerve implying its retrograde transport into the cell body as the process of lesion signal transmission. The present findings suggest that SMS may be involved in enhanced axonal regeneration via dynamic regulation of regeneration-associated proteins. KCI Citation Count: 2